The Influence of the Number Block Abacus on the Early Arithmetic Ability of 5 to 6 Year Old Children - Saputri, Cindah Ayu; Ilhami, Akmillah (Journal of English Language and Education, 2025)
Early childhood education is very important for the physical and mental development of children from birth to the age of six, when they experience rapid growth known as the " golden age ". Independence in numeracy, which includes the ability to name, sequence, add, and subtract numbers, is a crucial skill that needs to be taught. However, many early childhood children in Indonesia still face challenges in numeracy skills. This study aims to determine the effect of using a number block abacus on early numeracy skills in children aged 5-6 years at Az-Zahrah Islamic Kindergarten, Palembang. This study used a quantitative experimental method with a one-group pretest-posttest design. The research sample consisted of 14 children in class B5, obtained through structured test and observation techniques. The results showed that the average pretest score was 15.28, while the average posttest t score increased to 21.21, with a difference of 5.9. The results of the paired sample t-test showed a Sig. value. (2-tailed) of 0.000 0.05, which means there is a significant difference between the pretest and posttest. Thus, the number block abacus has an effect on children's early arithmetic abilities. The implications of this study provide insight for teachers and parents that the number block abacus can be used as a tool for stimulating children's cognitive, language, and fine motor skills.